Air traffic control safety indicators: what is achievable? - Brooker, Peter (European Organisation for the Safety of Air Navigation, 2006)
European Air Traffic Control is extremely safe. The drawback to this safety record is that it is very difficult to estimate what the ‘underlying’ accident rate for mid-air collisions is now, or to detect any changes over time. The aim is to see if it possible to construct simple ATC safety indicators that correlate with this underlying accident rate. A perfect indicator would be simple to comprehend and capable of being calculated by a checklist process. An important concept is that of ‘system control’: the ability to determine the outcome against reasonably foreseen changes and variations of system parameters. A promising indicator is ‘Incident Not Resolved by ATC’, INRA, incidents in which the ground ATC defences have been ‘used up’. The key question is: if someone says he or she knows how to make a good estimate of the underlying accident rate, then how could this claim be tested? If it correlates very well with INRA, then what would be the argument for saying that it is a better indicator?